2007
DOI: 10.1002/mus.20864
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurements in cubital tunnel syndrome

Abstract: The cubital tunnel is the most common site of ulnar nerve entrapment. Previous ultrasound studies have demonstrated enlargement of the ulnar nerve in cubital tunnel syndrome but did not report on the cubital tunnel itself. Twenty-two individuals with cubital tunnel syndrome were evaluated with nerve conduction studies and ultrasound. The ultrasound measurement that most strongly correlated with conduction velocity was the ratio of ulnar nerve to cubital tunnel cross-sectional area with the elbow flexed. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 11 publications
(15 reference statements)
4
34
0
Order By: Relevance
“…As we showed in a previous study, flexion and extension of the elbow does not alter measurements of ulnar nerve cross-sectional area at either the inlet or outlet of the cubital tunnel. 12 In conclusion, the ratio of the site of maximal swelling of the ulnar nerve around the elbow, compared with either a distal or proximal site along the nerve, differentiates those with UNE from controls. Although this technique does not appear to be more accurate than simply measuring the site of maximal swelling, a ratio of Ͼ1.5 may be informative for those with underlying polyneuropathy or obesity.…”
Section: Discussionmentioning
confidence: 94%
“…As we showed in a previous study, flexion and extension of the elbow does not alter measurements of ulnar nerve cross-sectional area at either the inlet or outlet of the cubital tunnel. 12 In conclusion, the ratio of the site of maximal swelling of the ulnar nerve around the elbow, compared with either a distal or proximal site along the nerve, differentiates those with UNE from controls. Although this technique does not appear to be more accurate than simply measuring the site of maximal swelling, a ratio of Ͼ1.5 may be informative for those with underlying polyneuropathy or obesity.…”
Section: Discussionmentioning
confidence: 94%
“…Many researchers have demonstrated ulnar nerve enlargement at the elbow and so suggested that ultrasonography is a beneficial tool for assessing ulnar neuropathy (Beekman et al, 2004;Norbury et al, 2011;Yoon et al, 2007;.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the previous studies in this field have focused only on the symptomatic ulnar nerves (Bayrak et al, 2010;Beekman et al, 2004;Yoon et al, 2007;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they do not provide information about the anatomy of the cubital tunnel. In this instance, ultrasonographic imaging plays an important role in helping to define the etiology of ulnar nerve compression [10]. Likewise, in this report, presenting an interesting cause of ulnar nerve entrapment, we emphasize the role of ultrasound in the diagnosis and treatment of peripheral nerve entrapment syndromes.…”
Section: Introductionmentioning
confidence: 86%